A dimensão subjetiva da educação empresarial: uma análise na perspectiva sócio-histórica - Oliveira, Roberta De Lima (2021)
Business education is a practice that seeks to develop professional skills and abilities in line with the organizational strategy, seeking to achieve better results. The constant changes brought about by technological advances, associated with the urgent need that humanity faces to solve the most profound and most complex social problems, imply several debates on the new skills needed by the future professional. Considering that it is through work that man fulfills himself and transforms his reality, this research has as its primary objective to investigate the subjective dimension of business education, identifying how it acts in human education and also how subjects build the educational phenomenon that takes place at work. Deep diving, this research presents as methodological assumptions the contributions of Sociohistorical Psychology, which, based on historical-dialectical materialism, uses as categories of analysis the meanings, contradiction, historicity, mediation, needs, among others. For this study, five women who work in different corporate learning contexts were interviewed: companies that invest in formal education and Corporate Universities or companies that have adopted a self-directed learning culture. The narratives were analyzed by elaborating the core meanings to infer the meanings constituted on the experiences of learning at work and which carry the materiality of labor relations that take place in the capitalist society in which the subjects are part. The analysis of the groups reveals the reasons for learning at work, who is interested in corporate learning, how the worker learns, and the relationship with the other. Business education is a powerful instrument that enables men to revolutionize labor relations by understanding the worker as a subject of reflection and action, creation and construction, active in the processes that constitute it. Understanding its subjective dimension allows us to apprehend the potentials and limitations of man in the exercise of work, promoting the discussion on the construction of a sustainable model of professional learning, which needs to be aligned with the current and future demands of society, and walking in favor of human emancipation